Maximizing your mini farm : self-sufficiency on 1/4 acre - Markham, Brett L. (Skyhorse Publishing, 2012)
Describes a holistic approach to small-area farming that shows how to produce a large amount of food on a quarter acre of land, providing tips on soil types, weed control, canning and preserving, and cooking for self-sufficiency.